A bibliometric analysis of the immune system and cognitive impairment: trends from 1985 to 2024 - Zou, Beibei; Xiang, Jinxi; Zhang, Muhua; Huang, Jing; Feng, Chao (Frontiers in Aging Neuroscience, 2025)
BackgroundCognitive impairment is closely linked to immune system dysfunction, with increasing research interest in the underlying mechanisms and potential therapeutic targets. Bibliometric analysis provides a comprehensive approach to understanding research trends, influential contributions, and emerging topics in this interdisciplinary field.MethodsThis study conducted a bibliometric analysis of publications related to the immune system and cognitive impairment from 1985 to 2024, retrieved from the Web of Science Core Collection. CiteSpace (6.4. R1), VOSviewer (1.6.20), and R-bibliometrix (R 4.3.0) were employed to analyze publication trends, co-authorship networks, keyword clustering, and co-citation patterns. Key metrics, including the H-index, G-index, and M-index, were computed to assess academic influence.ResultsA total of 3,737 publications were analyzed, revealing a significant increase in research output since 2021. The United States and China emerged as leading contributors, with a robust presence of collaborative networks. Keyword and co-citation analysis identified core research themes, including neuroinflammation, microglia activation, gut microbiota, TREM2-mediated immune responses, and inflammasomes. Emerging topics such as the gut–brain axis, metabolic syndromes, and immune regulation in neurodegenerative diseases have gained prominence in recent years. Highly cited papers highlighted the role of immune dysregulation in Alzheimer’s disease, multiple sclerosis, and HIV-associated neurocognitive disorders.ConclusionThis bibliometric analysis provides a comprehensive overview of research trends in immune-related cognitive impairment. The findings indicate an increasing focus on neuroinflammatory mechanisms, immune cell interactions, and novel immunotherapeutic strategies. Future research is expected to further explore the gut–immune–brain axis and precision medicine approaches in managing cognitive disorders. These findings may facilitate early detection strategies and novel interventions targeting immune–cognitive interactions, such as gut–brain axis modulation.